PHARMACOGNOSTICAL EVALUATION OF NAGAKESARA USED IN DIFFERENT PARTS OF INDIA - Suresh, Chaubey; Ramesh Chandra, Tewari; Rajeev, Kurele; Meeta, Kotecha; Gagan Deep, Kour (International Journal of Ayurveda and Pharma Research, 2015)
Nagakesara though have no mentioning in Vedic literature is a widely mentioned drug in the Ayurvedic classics both in Brihattrayees and Laghutrayees. In Nighantukaala Nagakesara included in almost all Nighantus which mentions its prime importance and wide utility in therapeutics especially in disorders of GIT, skin and bleeding disorders. It has more than 20 synonyms. Modern literature mentions its considerable role in bleeding disorders and explanation regarding its morphological characters, habitat, chemical composition, characters and action. There is a need to study the position of Nagakesara in the crude drug market. It was found that there is a lot of confusion regarding the acceptance of genuine drug under the name Nagakesara. As there is scarcity and unavailability of Nagkeshara, also due to lack of awareness, instead of Nagkeshara, the Pratinidhidravya like Surpunnag, Punnag, Tamalpatra are used commonly. And gradually the use of real Nagkesara is diminished and the Ayurvedic Vaidya, teachers and students also understood the Pratinidhidravyas of it as real Nagkeshara.